MULTIMODAL TRANSLATION IN SCIENTIFIC COMMUNICATION: CHALLENGES OF COMBINING TEXT, AUDIO AND VIDEO (International Conference on Educational Discoveries and Humanities, 2025)
This article explores the intricacies of multimodal translation in scientific communication, focusing on the simultaneous translation of textual, auditory, and visual elements. With the rise of digital scientific discourse, translators now face the complex task of rendering content across various modalities. Drawing from examples such as subtitled YouTube science lectures, podcast transcriptions, and academic video explainers, the article identifies key challenges including synchronicity, terminological coherence, cultural transference, and cognitive load. The study highlights the urgent need for integrated translation strategies that acknowledge multimodal semiotics and ensure conceptual accuracy in multilingual dissemination.